Hate Speech 2024 Presidential Candidates in Tiktok Account Comment Section from the Perspective of Social Media Literacy - Mery Anjeli Siregar; Teuku Azhari; Masithah Mahsa (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe the types of hate speech and the meanings contained therein. The type of research is descriptive qualitative. The research data consists of words and sentences containing hate speech obtained from the TikTok accounts of Gerindra, Detik.Com, Nasdem, Tempo.Co, Kompas.Tv, Gerald Vincent, and Rian Fahardhi. The data sources in this study are comments from TikTok accounts. The data collection techniques used in this study are reading, documentation, and note-taking. Based on the research findings, the most common type of hate speech is insults, with 46 data points, followed by defamation (12 data points), unpleasant behavior (2 data points), provocation (2 data points), and the spread of false news (2 data points). The types of lexical meaning found were 15 instances, grammatical meaning 21 instances, conceptual meaning 15 instances, and associative meaning 14 instances.